Generic substitution of antiepileptic drugs. (December 2010) - Sander, Josemir W; Ryvlin, Philippe; Stefan, Hermann; Booth, Daniel R; Bauer, Jürgen
Substitution of antiepileptic drugs with generic formulations may affect individual people, as well as healthcare systems. Analyses of large medical claims databases suggest that generic substitution of antiepileptic drugs is associated with increased morbidity and greater use of healthcare resources. While a single brand-to-generic switch may be associated with a slight increase in overall medical costs, multiple switches may be associated with higher costs, perhaps because different generic agents are not required to be bioequivalent to each other. Generic substitution also affects the individual: along with the possible increased risk of seizures or adverse events, inconsistency of supply may make the medication appear unfamiliar, thus discouraging adherence. Importantly, substitution is often carried out at the dispensing level, without the knowledge or consent of physicians and affected individuals. Therefore, regulatory and professional bodies advocate that substitution should not be carried out without specific counseling of the individual by healthcare professionals on the details and implications of the change.